Model Kemitraan Strategis Pada Bisnis Ritel (Kajian Komunikasi Bisnis Pada Kampanye Pengurangan Penggunaan Kantong Plastik) - Rahyang Nusantara (Jurnal Universitas Paramadina, 2017)
In support of achieving Sustainable Development Goals (SDGs), partnerships among stakeholders are essential. Some efforts to reduce plastic bags occurs jointly by the government, retailers, and community groups and consumers in 2016 through “pay for plastic bags” trials managed to reduce plastic bags consumption up to 55%. Although these efforts are suddenly stopped, it needs to be continued to be applied consistently as a support to achieving SDGs, especially on the Goal 12 (Responsible Consumption and Production). The purpose of the research is to address this challenge on reducing plastic bags consumption. The research method is qualitative with the approach of human-centered design and co-creation technique that brings government, retailers, consumer groups, mass media and creative industries to sit together to create a communication strategy to reduce the demand of plastic bags in retail. The goals of the research are communication strategy and program ideas and sustainable partnership model.